Compensation Management and Employee Wellbeing of Academic Staff in Ugandan Private Universities during COVID-19 Lockdown - Mugizi, Wilson; Rwothumio, Joseph; Amwine, Christopher M. (Interdisciplinary Journal of Education Research, 2021)
This study examined the impact of compensation management on academic staff's employee well-being in private universities in Uganda during the COVID-19 lockdown. Two dimensions of compensation management considered were compensation determination and compensation administration. Employee well-being was studied in terms of psychological well-being, social well-being, workplace well-being and subjective well-being. This study used a cross-sectional design on a sample of academic staff from five private universities. Factor analysis was used to identify key items of compensation management and employee well-being, followed by descriptive, correlation and multiple regression analyses. Multiple regression analysis assessed the magnitude and strength of the impact of compensation management on employee well-being. The results supported the hypotheses on the influence of compensation determination and administration on employee well-being. Therefore, compensation determination and administration are important in enhancing the academic staff's well-being in private universities in contingent situations such as COVID-19 lockdown. In managing compensation issues in contingent situations, managers of private universities should determine and administer compensation considering employees' interests. This study adds to the scanty literature on compensation management and employee wellbeing. It identifies compensation management factors that organisations should consider to promote employee well-being in contingent situations.
Keywords: Compensation administration; Determination; Employee well-being management; Psychological; Social; Subjective; Workplace